PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF MORAL QUALITIES OF ADOLESCENTS IN THE PROCESS OF BOXING - G. R. Matkarimov; U. Ya. Dustmurodov (Galaxy International Interdisciplinary Research Journal, 2024)
The model of process of moral education of teenage boxers and pedagogical potential of boxing locates in work as means of formation of moral qualities and values. Formed a methodological basis of research of the provision of psikhologo-pedagogical works about physical training as a factor of moral development of the personality. For the solution of research problems the complex of methods was used: synthesis of pedagogical experience; long supervision over sports activity of pupils; creation of pedagogical situations, conversations, interview; control measurements. Results of approbation of pedagogical model of process of education of teenage boxers in the conditions of sports section are presented, the main pedagogical situations in logic of this process are described. Levels of formation of moral qualities of teenage boxers, methods of their education are presented. Relationships of cause and effect of interaction of teenagers in system "the teenager - the trainer - children’s sports collective" as direct source and educational tool of moral qualities of the personality in the course of occupations by boxing are revealed.